Growth and Feed Digestibility of Sangkuriang Catfish with Corn Gluten Meal-Based Feeding. Issue 1 (1st February 2022) - Mustahal,; Hermawan, D; Syamsunarno, M B; Agung, L A; Nurhaliza, A S; Rachmawati, R F; Anggraeni, D; Putra, A N
Abstract: Diet testing was conducted for 50 days to investigate the growth and feed digestibility of Sangkuriang catfish with corn gluten meal (CGM)-based feeding. This involved 5 treatments with different levels of CGM in the feed 0, 75, 150, 225, and 300 g.kg −1 for three replications. The result showed that the value of SGR ranged from 0.87 to 1.51 %.day −1, the SGR values with CGM at 0, 75 and 150 g.kg −1 were significantly higher than the values in CGM 225 and 300 g.kg −1 . The best value of protein and lipid digestibility were recorded with CGM at 0, 75 and 150 g.kg −1 compared to CGM at 225 and 300 g/kg. A greater propensity for higher CGM levels to negatively impact on growth and feed digestibility of Sangkuriang catfish. Therefore, CGM is confirmed to process the potential for application at a level of 150 g.kg −1 in the Sakuriang catfish diet without negatively influencing growth and feed digestibility.